Dynamics of Bose-Einstein condensates in cigar-shaped traps - Kamchatnov, A. M.; Shchesnovich, V. S. [UNESP] (American Physical Society (APS), 2004)
The dynamics of Bose-Einstein condensates (BEC) were investigated in the cigar-shaped trap by means of a variational approach. The system was found to depend on one spatial coordinate, which can greatly simplify numerical simulations of nonlinear effects in BEC. It was found that the dispersions relations for the sound and radial compression waves are obtained in a wide region of values of the condensate density. It was shown that bright solitons can propagate along dense enough repulsive BEC confined in a cigar-shaped trap.